“The Pen is Mightier than the Sword”: Popular Ethics in Edo Period Japan (Global Journal of Human-Social Science, 2023)
By the end of the Edo period of Japan 1603 1868 the three major religious traditions of Japan each appear to have found formally defined roles within Japanese culture and politics In the mid-19 th century N Sontoku 1787 1858 succinctly summarized his understanding of their more formalized roles as follows Shinto is the way which provides the foundation of the country Confucianism is the way which provides for governing the country and Buddhism is the way which provides for governing one s mind
Keywords: edo; tokugawa; ancient learning; national learning; hirata shinto; kyoto; meiji